Survival differences between European and US patients with colorectal cancer: role of stage at diagnosis and surgery. Issue 2 (11th January 2005) - Ciccolallo, L; Capocaccia, R; Coleman, M P; Berrino, F; Coebergh, J W W; Damhuis, R A M; Faivre, J; Martinez-Garcia, C; Møller, H; Ponz de Leon, M; Launoy, G; Raverdy, N; et al.
Abstract : Background: Population based colorectal cancer survival among patients diagnosed in 1985–89 was lower in Europe than in the USA (45% v 59% five year relative survival). Aims: To explain this difference in survival using a new analytic approach for patients diagnosed between 1990 and 1991. Subjects: A total of 2492 European and 11 191 US colorectal adenocarcinoma patients registered by 10 European and nine US cancer registries. Methods: We obtained clinical information on disease stage, number of lymph nodes examined, and surgical treatment. We analysed three year relative survival, calculating relative excess risks of death (RERs, referent category US patients) adjusted for age, sex, site, surgery, stage, and number of nodes examined, using a new multivariable approach. Results: We found that 85% of European patients and 92% of US patients underwent surgical resection. Three year relative survival was 69% for US patients and 57% for European patients. After adjustment for age, sex, and site, the RER was significantly high in all 10 European populations, ranging from 1.07 (95% confidence interval 0.86–1.32) (Modena, Italy) to 2.22 (1.79–2.76) (Thames, UK). After further adjustment for stage, surgical resection, and number of nodes examined (a determinant of stage), RERs ranged from 0.77 (0.62–0.96) to 1.59 (1.28–1.97). For some European registries the excess risk was small and not statistically significant. Conclusions: US-Europe survival differences in colorectal cancer are large but seem to be mostly attributable to differences in stage at diagnosis. There are wide variations in diagnostic and surgical practice between Europe and the USA.